Non-classic congenital adrenal hyperplasia due to 21-hydroxylase deficiency: laboratory criteria for the diagnosis and control of treatment efficacy - O.V. Rykova (Mìžnarodnij Endokrinologìčnij Žurnal, 2019)
Non-classic congenital adrenal hyperplasia (NCAH) due to 21-hydroxylase deficiency is one of the actual causes of hyperandrogenic manifestations at different age intervals. Timely diagnosis of the disease requires evaluating basal 17-hydroxyprogesterone levels during the comprehensive examination of patients of different age groups with clinical manifestations of androgen excess. This is especially important when examining adolescent girls and women of reproductive age with signs of hyperandrogenism. The obligatory examination of women when establishing the diagnosis of polycystic ovary syndrome should include the exclusion of non-classical NCAH according to all world recommendations. When 17-hydroxyprogesterone levels are in the range of 2–10 ng/ml, it is necessary to carry out cosyntropin stimulation test, which is recognized worldwide as the standard of NCAH diagnosis. The diagnostic threshold for NCAH diagnosis due to 21-hydroxylase deficiency is a level of 17-hydroxyprogesterone, basal or stimulated in cosyntropin test, higher than 10 ng/ml. Genetic testing — determining mutations in the CYP21A2 gene — is an important and necessary tool not only to confirm the diagnosis, but also to identify treatment of the patient with the diagnosis of NCAH and to determine the risk of emergence of a classic form in an unborn child in the presence of allele associated with classic САН. The recent recommendations from 2018 Congenital Adrenal Hyperplasia Due to Steroid 21-Hydroxylase Deficiency: An Endocrine Society Clinical Practice Guideline are taken as the basis of the laboratory diagnostic criteria.